Exploring Students’ Speaking Anxiety in Story Completion Technique In EFL Classroom - Viviana, Yulianti; Samsi, Yogi Setia (Journal of Education For Sustainable Innovation, 2023)
Speaking is a form of speech act in the form of sounds produced by the speech apparatus accompanied by body movements and facial expression. Unfortunately, many students find it difficult to practice this because of excessive anxiety. One example of anxiety that we often encounter is public speaking anxiety. Anxiety is a tendency where a person is reluctant to his abilities. In this research, the researcher will use case study design. The type of this research was descriptive qualitative. This research focused in investigated speaking anxiety with story completion technique in EFL Classroom. This research was conducted at a high school in West Bandung Regency. Researchers chose this school because researchers are alumni of this school.The results of the analysis, In short, we can consider that speaking is one of the instruments to talk to each of them others in everyday life, because human life speaks very important because we can provide insights, data, news, thoughts. However, speaking in English for students is difficult because students need to communicate in other dialects with high self-confidence.However, students must be active in the classroom because speaking skills can improve with practice. They must also pay attention and respect each other not laugh at anyone when he makes a mistake in speaking. Students must be aware that making mistakes means the teaching and learning process is ongoing.